Evaluating the impact of the Vavilov-Frankel Fellowship Programme - Gotor, Elisabetta; Cherfas, J. (2012)
The Vavilov-Frankel Fellowship Programme awards two fellowships annually to young scientists from developing countries, to enable them to carry out innovative research on the conservation and use of plant genetic resources (PGR). Since 1994, 39 scientists from 24 countries have taken part in the programme. An evaluation of the impact of the Vavilov-Frankel Fellowships (VFF) reveals that overall the VFF Programme has met its stated goals of contributing to the scientific capacity of the Fellows and their home institutes, and of fostering the conservation and use of PGR. The evaluation also indicated ways in which the Fellowship Programme could be improved, and these are now being implemented.